1995
DOI: 10.1007/bf01857871
|View full text |Cite
|
Sign up to set email alerts
|

What does potential for hostility measure? Gender differences in the expression of hostility

Abstract: We examined the construct validity of Potential for Hostility (PH) for healthy undergraduate males and females. In Study 1, 45 males and 76 females were rated for PH. Subjects then completed the Cook Medley Hostility Scale (Ho) and a trait negative affectivity (NA) scale. For males, PH correlated with Cynicism, a subscale of the Ho, but was unrelated to NA. However, for females, PH was unrelated to self-reported hostility and minimally related to NA. In Study 2, 52 males and 91 females again were rated for PH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Independent judges' ratings of the overall degree of anger apparent in the transcripts of participants' interviews were significantly predicted by the hostility components of aggressive It is not surprising that the analysis of participants' use of evaluative words revealed that female participants and those who scored higher in social desirability tended to use words that are scored as more affectively positive on the DAL. Socialization into gender roles is one process that is clearly believed to exert an impact on the expression, and even the experience of hostile sentiments and angry affect (Brody, 1985;Davidson and Hall, 1995). Sanctions against males for the expression of anger are believed to be less than those against females (Brody, 1985).…”
Section: Discussionmentioning
confidence: 97%
“…Independent judges' ratings of the overall degree of anger apparent in the transcripts of participants' interviews were significantly predicted by the hostility components of aggressive It is not surprising that the analysis of participants' use of evaluative words revealed that female participants and those who scored higher in social desirability tended to use words that are scored as more affectively positive on the DAL. Socialization into gender roles is one process that is clearly believed to exert an impact on the expression, and even the experience of hostile sentiments and angry affect (Brody, 1985;Davidson and Hall, 1995). Sanctions against males for the expression of anger are believed to be less than those against females (Brody, 1985).…”
Section: Discussionmentioning
confidence: 97%
“…In our previous two studies, women's Polio scores were unrelated to trait and state self-reported hostility, but were positively related to trait and state Negative Affect (Davidson and Hall, 1995). Consequently, we concluded that Polio appeared to assess an experiential, or neurotic hostility dimension in women.…”
Section: Introductionmentioning
confidence: 49%
“…We also found that these same measures were related to lower resting SBP, nonhypertensive status, Antagonism, as well as Neuroticism, in women. However, it is important to note that the differential relation between Neuroticism and Polio was not significantly different between men and women in this study, as it was in our previous studies (Davidson and Hall, 1995). In our previous studies, Neuroticism was measured by a trait and state measure of Negative Affectivity, one of the many facets of Neuroticism (Watson and Pennebaker, 1989).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations